Modelling the retirement planning among staff in a public university by using multiple linear regression - Amirah Fatini Berahim @ Ab Rahman; Wan Nurul Fathihah Wan Ahmad Fekri; Noor Zafarina Mohd Fauzi; Shamsunarnie Mohamed Zukri; Nor Hazreeni Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2022)
Retirement is a stage in life when a person decides to leave the workforce permanently. In Malaysia, the typical retirement age is 65. Individuals can predict how quickly and likely they will be able to reach their retirement goals with good retirement planning. Hence, the purpose of this study is to identify the determinants of retirement planning which are health, job environment, and financial planning among staffs in a public university in Kelantan. In this study, 85 samples were selected using a stratified random sampling technique that involve academic and non-academic staff. The data were collected using questionnaire that was distributed via WhatsApp and e-mail. To achieve the objectives, the data was analyzed using Multiple Linear Regression. From this study, it can be concluded that there are two variables that significantly influence retirement planning which are health, and financial planning. In conclusion, individuals are advised to take good care of their health, and it is advisable for individuals to have investment property for future saving.